Selective Induced Altered Coccidians to Immunize and Prevent Enteritis - Helieh S. Oz (Gastroenterology Research and Practice)
Microbiomic flora in digestive tract is pivotal to the state of our health and disease. Antibiotics affect GI, control composition of microbiome, and shift equilibrium from health into disease status. Coccidiosis causes gastrointestinal inflammation. Antibiotic additives contaminate animal products and enter food chain, consumed by humans with possible allergic, antibiotic resistance and enigmatic side effects. Purposed study induced nonpathogenic, immunogenic organisms to protect against disease and abolish antibiotics’ use in food animals and side effects in man. Diverse species of Coccidia were used as model. Immature organisms were treated with serial purification procedure prior to developmental stages to obtain altered strains. Chicks received oral gavage immunized with serial low doses of normal or altered organisms or sham treatment and were challenged with high infective normal organisms to compare pathogenicity and immunogenicity. Mature induced altered forms of E. tenella and E. necatrix lacked developmental stage of “sporocysts” and contained free sporozoites. In contrast, E. maxima progressed to normal forms or did not mature at all. Animals that received altered forms were considerably protected with higher weight gain and antibody titers against challenge infection compared to those that received normal organisms (p<0.05). This is the first report to induce selected protective altered organisms for possible preventive measures to minimize antibiotic use in food animals.